Impacts of forest conversion and agriculture practices on water pathways in Southern Brazil. Issue 15 (28th June 2018) - Robinet, Jérémy; Minella, Jean P. G.; de Barros, Cláudia A. P.; Schlesner, Alexandre; Lücke, Andreas; Ameijeiras-Mariño, Yolanda; Opfergelt, Sophie; Vanderborght, Jan; Govers, Gerard
Abstract: Land‐use/cover change (LUCC), and more specifically deforestation and multidecadal agriculture, is one of the various controlling factors of water fluxes at the hillslope or catchment scale. We investigated the impact of LUCC on water pathways and stream stormflow generation processes in a subtropical region in southern Brazil. We monitored, sampled and analysed stream water, pore water, subsurface water, and rainwater for dissolved silicon concentration (DSi) and 18 O/ 16 O (δ 18 O) signature to identify contributing sources to the streamflow under forest and under agriculture. Both forested and agricultural catchments were highly responsive to rainfall events in terms of discharge and shallow groundwater level. DSi versus δ 18 O scatter plots indicated that for both land‐use types, two run‐off components contributed to the stream discharge. The presence of a dense macropore network, combined with the presence of a compact and impeding B‐horizon, led to rapid subsurface flow in the forested catchment. In the agricultural catchment, the rapid response to rainfall was mostly due to surface run‐off. A 2‐component isotopic hydrograph separation indicated a larger contribution of rainfall water to run‐off during rainfall event in the agricultural catchments. We attributed this higher contribution to a decrease in topsoil hydraulic conductivity associated with agricultural practices. The chemical signature of the old water component in the forested catchment was very similar to that of the shallow groundwater and the pore soil water: It is therefore likely that the shallow groundwater was the main source of old water. This is not the case in the agricultural catchments where the old water component had a much higher DSi concentration than the shallow groundwater and the soil pore water. As the agricultural catchments were larger, this may to some extent simply be a scale effect. However, the higher water yields under agriculture and the high DSi concentration observed in the old water under agriculture suggest a significant contribution of deep groundwater to catchment run‐off under agriculture, suggesting that LUCC may have significant effects on weathering rates and patterns.